PERTANGGUNGJAWABAN ASURANSI SOSIAL PADA PT. JASA RAHARJA (PERSERO) TERHADAP KECELAKAAN PENUMPANG UMUM OLEH PT. JASA RAHARJA CABANG MEDAN - Agus Jonatan P; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Insurance cover or simply organize the restitution of a loss that can be measured by money. Insurance amount of money set up insurance that provides compensation amount as had been agreed previously and there should be no relationship between the loss suffered by the amount of money given by the person indursnce. an important element in the event of insurance contained in the formulation of Article 246 of the Commercial code is for damages. These elements refer only to the insurance (loss insurance) whose object is wealth. Life insurance (life insurance) are not included in the formulation of Article 246 of the Commercial code, because the human spirit is not wealth.This type of research is classified in socio-juridical kind of research, because this research peneluis directly conduct research on the location or place gambara examined in order to provide complete and clear about the issues examined. This research was conducted at Jasa Raharja Branch Medan, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, flat secondary data tertiary, data collection techniques in this study through interviews and a review of the literature.From the research there are three main issues that can be inferred, first, Accountability Social Insurance held by Jasa Raharja is already going well but there is still yet to be done properly and not in accordance with the provisions stipulated in Law Number. 33 Year 1964 About the Fund Coverage Compulsory Accident passengers because many victims find it difficult bureaucracy in the management of compensation and does not fit in the disbursement of compensation, the compensation arrangement and doesn’t fit in the disbursement. faced by Jasa Raharja in social insurance liability on public passenger accident victim is in handling the victims or heirs of the victim that is non accessories files maintenance requirements Prog compensation fund as stated in the regulations, third, The efforts made by Jasa Raharja in the face of obstacles in the social insurance liability accident passengers that is by holding public dissemination to the public, students and students about the benefits kcelakaan road traffic and public passenger accident given by Jasa Raharja, the socialization of the rights and obligations of the victim or the victim's heirs againstKeywords: General Accident - Insurance Social - Responsibil